Historical and Religious Controversy in the Novel '' Mudnibon lawno damihim fi kaffi '' by AL-HABIB AL-SAIH - TALHA, Abdelbasst; BOULADJINE , Kadeur (Milev Journal of Research and Studies, 2020)
The novel “Miudnibon lawno damihim fi kaffi ” explores an important historical stage in the contemporary path of Algeria. The novel talks about a victim of terrorist groups who found himself without a family, as the latter was subjected to comprehensive annihilation by the extremist group “Lahwel”, so he decided The young man took revenge on his own, rejecting all the solutions offered. Because of the game imagined, the novel embodied the tragedy of a people, a generation, or a clash of a number of generations, as it dealt with the events of a unique stage in the contemporary history of Algeria. The hidden struggle between history and extremism.